The Influence of Millennial Leadership, Organizational Culture on Employee Performance Mediated by Job Satisfaction - Novel, Putri Irma; Suwarto, FX (Jurnal Locus Penelitian dan Pengabdian, 2026)
This research aims to explore the relationship between millennial leadership, organizational culture, and employee performance, with job satisfaction acting as a mediating factor. The study focuses on the hotel industry, which faces increasing competition and rapid changes, particularly in leadership and work culture. While previous research has examined the effects of corporate culture and millennial leadership on employee performance and job satisfaction, none have investigated job satisfaction as a mediator in this context. The study involved 201 hotel employees from various businesses in Jakarta, using purposive sampling. Data analysis was performed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results show that all variables significantly impact the hypotheses. Job satisfaction was found to mediate the relationship between organizational culture and millennial leadership, both of which positively affect employee performance. The study concludes that millennial leadership can enhance employee job satisfaction, improve organizational culture, and boost employee performance. Effective leadership and organizational culture strategies are essential for improving work conditions and increasing job satisfaction, ultimately enhancing employee performance in the hotel industry.